Analysis of the stereotype as a literary image: a study proposal - Ángeles Galiano, Teresa de Jesús (Tropelías: Review of Literary Theory and Comparative Literature, 2023)
This article proposes a study methodology for the analysis of stereotypes as textual images, preceded by a theoretical presentation on the most relevant aspects of Imagology and the main existing studies on the textual approach to images. In the first place, the antecedents of the imagological system will help to present the subsequent justification of the proposed method and, through the compilation of relevant research; the components of the scheme and its argumentation are shown.
Keywords: Literary Aesthetics; literary analysis; literary language; cultural identity; Literary Terms